The Learning Trajectory of Sphere Using Megono Gunungan Tradition Context - Nursyahidah, Farida; Saputro, Bagus Ardi; Albab, Irkham Ulil (Universitas Ahmad Dahlan, 2021)
This study aims to develop a learning trajectory by utilizing the local wisdom of the Megono Gunungan tradition to help students grasp the sphere's notion. This research applied the approach of the Indonesian Realistic Mathematical Approach (PMRI). Ninth-grade students at SMP 38 Semarang, Central Java, Indonesia, were the subjects of this study. The methodology used is based on Graveimeijer and Cobb's three steps of design research: preliminary design, design experiment, and retrospective analysis. Numerous data collection methods were used, involving video, photography, the outcome of students' worksheets, and student interviews. The learning trajectory comprises four activities: identifying sphere components using the Megono Gunungan tradition interactive video context, discovering the sphere surfaces area using orange fruit, finding the sphere's volume through rice media, and solving problems of the sphere. This study's findings signify that the utilization of the Megono Gunungan tradition context could encourage learners to recognize the concept of the sphere through a sequence of designed activities.